Ion trapping by dust grains: Simulation applications to the Enceladus plume. Issue 4 (22nd April 2017) - Farrell, W. M.; Wahlund, J.‐E.; Morooka, M.; Kurth, W. S.; Gurnett, D. A.; MacDowall, R. J.
Abstract: Using a particle‐in‐cell electrostatic simulation, we examine the conditions that allow low‐energy ions, like those produced in the Enceladus plume, to be attracted and trapped within the sheaths of negatively charged dust grains. The conventional wisdom is that all new ions produced in the Enceladus plume are free to get picked up (i.e., accelerated by the local E field to then undergo vB acceleration). However, we suggest herein that the presence of submicron‐charged dust in the plume impedes this pickup process since the local grain electric field greatly exceeds the corotation E fields. The simulations demonstrate that cold ions will tend to accelerate toward the negatively charged grains and become part of the ion plasma sheath. These trapped ions will move with the grains, exiting the plume region at the dust speed. We suggest that Cassini's Langmuir probe is measuring the entire ion population (free and trapped ions), while the Cassini magnetometer detects the magnetic perturbations associated with pickup currents from the smaller population of free ions, with this distinction possibly reconciling the ongoing debate in the literature on the ion density in the plume. Key Points: The Enceladus plume contains neutrals, newly formed ions, and dust, and the dust can influence ion trajectories Without dust, ions are free to get picked up by the local corotating magnetoplasma Our simulations show that with added dust, the large E fields from the grain charge disrupts pickup and creates ion trapping